Acute vasoreactivity testing in pediatric idiopathic pulmonary arterial hypertension: an international survey on current practice. (1st November 2019) - Caicedo, Lina; Hopper, Rachel; Garcia Aguilar, Humberto; Ivy, Dunbar; Haag, Dora; Fineman, Jeff; Humpl, Tillman; Al‐Tamimi, Omar; Feinstein, Jeff A.; Berger, Rolf; Rosenzweig, Erika; Kashour, Tarek; et al.
Abstract : The aim of this study was to determine practice patterns and inter‐institutional variability in how acute vasoreactivity testing (AVT) is performed and interpreted in pediatrics throughout the world. A survey was offered to physicians affiliated with the Pediatric & Congenital Heart Disease Taskforce of the Pulmonary Vascular Research Institute (PVRI), the Pediatric Pulmonary Hypertension Network (PPHNET), or the Spanish Registry for Pediatric Pulmonary Hypertension (REHIPED), from February to December 2016. The survey requested data about the site‐specific protocol for AVT and subsequent management of pediatric patients with idiopathic pulmonary arterial hypertension (IPAH) or heritable PAH (HPAH). Twenty‐eight centers from 13 countries answered the survey. AVT is performed in most centers using inhaled nitric oxide (iNO). Sitbon criteria was used in 39% of the centers, Barst criteria in 43%, and other criteria in 18%. First‐line therapy for positive AVT responders in functional class (FC) I/II was calcium channel blocker (CCB) in 89%, but only in 68% as monotherapy. Most centers (71%) re‐evaluated AVT‐positive patients hemodynamics after 6–12 months; 29% of centers re‐evaluated based only on clinical criteria. Most centers (64%) considered a good response as remaining in FC I or II, with near normalization of pulmonary arterial pressure and pulmonary vascular resistance, but a stable FC I/II alone was sufficient criteria in 25% of sites. Protocols and diagnostic criteria for AVT, and therapeutic approaches during follow‐up, were highly variable across the world. Reported clinical practice is not fully congruent with current guidelines, suggesting the need for additional studies that better define the prognostic value of AVT for pediatric IPAH patients.